Effects of Co-60 gamma irradiation on the surface morphology and magnetic properties in thin film permalloy Ni80Fe20 for magnetic sensor. Issue 1 (February 2021) - Ismail; Priyantoro, D; Oktaria, V; Purnama, B
Abstract: The thin film of permalloy Ni80 Fe20 were synthesized by electro-deposition method on PCB substrate. Then the sample irradiated by using Co-60 gamma for 20 Gy and 30 Gy. The sample were investigated by scanning electron microscopy and vibrating sample magnetometer, before and after gamma irradiation process by Co-60 gamma irradiation. The decrease in grain size with the increase of radiation dose is observed. The hysteresis curve also showed an increase in saturation magnetization with the increase of radiation dose from 708 emu/cc to 920 emu/cc. The investigation results indicate that the modification of the surface-microstructure samples by gamma irradiation change a magnetic properties in thin film permalloy Ni80 Fe20 .